MicroRNA-383: A tumor suppressor miRNA in human cancer - Jafarzadeh, Abdollah; Noori, Majid; Sarrafzadeh, Shaghayegh; Tamehri Zadeh, Seyed Saeed; Nemati, Maryam; Chatrabnous, Nazanin; Jafarzadeh, Sara; Hamblin, Michael R; Jafari Najaf Abadi, Mohammad Hassan; Mirzaei, Hamed (Frontiers in Cell and Developmental Biology, 2022)
Downregulated expression of anti-tumor miR-383 has been found in many kinds of cancer. MiR-383 family members can directly target the 3′-untranslated region (3′-UTR) of the mRNA of some pro-tumor genes to attenuate several cancer-related processes, including cell proliferation, invasion, migration, angiogenesis, immunosuppression, epithelial-mesenchymal transition, glycolysis, chemoresistance, and the development of cancer stem cells, whilst promoting apoptosis. Functionally, miR-383 operates as a tumor inhibitor miRNA in many types of cancer, including breast cancer, hepatocellular carcinoma, gastric cancer, pancreatic cancer, colorectal cancer, esophageal cancer, lung cancer, head and neck cancer, glioma, medulloblastoma, melanoma, prostate cancer, cervical cancer, oral squamous cell carcinoma, thyroid cancer, and B-cell lymphoma. Both pro-tumor and anti-tumor effects have been attributed to miR-383 in ovarian cancer. However, only the pro-tumor effects of miR-383 were reported in cholangiocarcinoma. The restoration of miR-383 expression could be considered a possible treatment for cancer. This review discusses the anti-tumor effects of miR-383 in human cancers, emphasizing their downstream target genes and potential treatment approaches.